Microstructures and mechanical properties of reactive spark plasma-sintered ZrB2–SiC–MoSi2 composites. Issue 19 (1st October 2022) - Zhu, Mingcheng; Zhang, Lan; Li, Na; Cheng, Desen; Zhang, Jidong; Yu, Shiyao; Bai, Hui; Ma, Huizhong
Abstract: Ternary ZrB2 –SiC–MoSi2 composites with different nominal volume fractions of SiC (10–25 vol%) and MoSi2 (5–20 vol%) were sintered by reactive spark plasma sintering (RSPS) at 1650 °C and 35 MPa from the starting powders of ZrB2, Si, Mo and activated charcoal. The densification behaviour, microstructures and mechanical properties were comprehensively investigated. SiC clusters and MoSi2 were formed by in-situ reactions and the improved sintering efficiency was attributed to the mass transfer by liquid Si. The formation of a core–shell (Zr, Mo)B2 solid solution was confirmed by X-ray diffraction (XRD) and scanning electron microscopy (SEM). With the addition of the nominal MoSi2 content up to 15 vol%, the molar ratio of MoB2 in the solid solution shell increased owing to the increase of Mo; the densification and mechanical properties decreased owing to the softness of MoSi2, the cracks, and the large size of SiC clusters. The relative density, Vickers hardness, and fracture toughness of ZrB2 –SiC–MoSi2 composites were significantly better than those of bulk ZrB2 owing to the combined effect of phase enhancement and solid solution strengthening.